Faktor-faktor Kunci Penerapan Bangunan RISHA pada Proyek Penanganan Pasca Bencana Gempa di Cianjur - Komaludin, Kamal; Soekiman, Anton; Siregar, Chandra Afriade (Jurnal Talenta Sipil, 2026)
The implementation of Simple Healthy Instant Houses (RISHA) as a temporary or permanent housing solution after an earthquake has become a strategic choice for the Indonesian government. RISHA is designed to be built quickly, affordably, and earthquake-resistant. However, in its implementation, there are various challenges that hinder the effectiveness and efficiency of the implementation of this system. The purpose of this study is to identify and evaluate the main obstacles in the implementation of RISHA buildings in post-earthquake rehabilitation projects, including technical, social, and institutional aspects. This study uses a qualitative method with a case study approach focused on the earthquake-affected area in Cianjur Regency. The results of the study indicate that the main challenges include limited understanding of the local community and workforce regarding the RISHA modular system, the availability of materials and structural components at the disaster site, limited training time, and lack of coordination between stakeholders. In addition, the cultural and architectural preferences of the local community also affect the level of acceptance of the RISHA building model. Thus, a more comprehensive and participatory approach is needed in the implementation of RISHA in order to increase its effectiveness as a sustainable post-disaster solution.